Determining functional activity profiles in patients with upper extremity disorders: is there effect modiﬁcation by hand grip strength? - Kim MJ; Park KS; Seo AR; Lee SI; Ha YC; Yoo JI (Clinical Interventions in Aging, 2018)
Mi-Ji Kim,1–3 Ki Soo Park,1–3 Ae-Rim Seo,1,2 Sang-Il Lee,4 Yong-Chan Ha,5 Jun-Il Yoo2,3,6 1Department of Preventive Medicine, Gyeongsang National University College of Medicine, Jinju, Republic of Korea; 2Institute of Health Sciences, Gyeongsang National University College of Medicine, Jinju, Republic of Korea; 3Center for Farmer’s Safety and Health, Gyeongsang National University Hospital, Jinju, Republic of Korea; 4Department of Internal Medicine, Institute of Health Sciences, Gyeongsang National University School of Medicine, Gyeongsang National University Hospital, Jinju, Republic of Korea; 5Department of Orthopedic Surgery, Chung-Ang University Hospital, Seoul, Republic of Korea; 6Department of Orthopedic Surgery, Gyeongsang National University Hospital, Jinju, Republic of Korea Purpose: The purposes of this study were to investigate the effect of hand-grip strength (HGS) on the Disabilities of the Arm, Shoulder, and Hand (DASH) score in women with upper extremity musculoskeletal disorders (UEMDs) living in rural communities and examine whether upper extremity diseases affected upper extremity functional activity in each group (normal/low HGS) and whether grip strength (GS) was an effect modifier in upper extremity functional activity. Methods: A total of 239 women older than 60 years who had completed a medical workup for epicondylitis, rotator cuff tears, and/or hand osteoarthritis were included in the final study. Functional activity was assessed by DASH, and muscle strength was measured by GS. Low HGS was defined according to the Asian Working Group for Sarcopenia (HGS <18 kg in women). Pearson correlation analysis was performed to evaluate the relationship between HGS and the DASH score. A multiple regression analysis was performed after defining DASH as a dependent variable and dividing subjects into two groups (low HGS and normal HGS). Statistical analyses were performed using SPSS Statistics V.24. Results: HGS in the participants correlated with the DASH score (r=-0.320, P<0.001). In the low HGS group, waist circumference (B=-0.526, P=0.010) and the DASH score were significantly correlated. In addition, DASH scores were statistically significantly increased as the number of upper extremity diseases increased to 2 (B=11.592, P=0.016) and 3 (B=15.716, P=0.001). The DASH score in the normal HGS group was correlated with the Patient Health Questionnaire-2 score (β=2.680, P<0.001) after adjusting covariates. Conclusion: We found that HGS in UEMD patients affected health-related quality of life as measured by the DASH. Maintaining hand muscle strength may improve patient functional activity in age-related UEMDs. Keywords: hand-grip strength, quality of life, aging, rural, upper extremity musculoskeletal disorders, functional activity